Micro-scale testing and micromechanical modelling for high cycle fatigue of CoCr stent material. (June 2015) - Sweeney, C.A.; O׳Brien, B.; Dunne, F.P.E.; McHugh, P.E.; Leen, S.B.
Abstract: This paper presents a framework of experimental testing and crystal plasticity micromechanics for high cycle fatigue (HCF) of micro-scale L605 CoCr stent material. Micro-scale specimens, representative of stent struts, are manufactured via laser micro-machining and electro-polishing from biomedical grade CoCr alloy foil. Crystal plasticity models of the micro-specimens are developed using a length scale-dependent, strain-gradient constitutive model and a phenomenological (power-law) constitutive model, calibrated from monotonic and cyclic plasticity test data. Experimental microstructural characterisation of the grain morphology and precipitate distributions is used as input for the polycrystalline finite element (FE) morphologies. Two microstructure-sensitive fatigue indicator parameters are applied, using local and non-local (grain-averaged) implementations, for the phenomenological and length scale-dependent models, respectively, to predict fatigue crack initiation (FCI) in the HCF experiments. Graphical abstract: Highlights: Microstructural characterisation and HCF testing of CoCr foil specimens is presented. A micromechanical framework for CoCr stent fatigue is developed and validated. Indicator parameters, calibrated from LCF data, successfully capture HCF behaviour. A phenomenological CP model is suitable for analysis of comparable microstructures. A strain-gradient, non-local CP model is recommended for dissimilar microstructures.